Systems thinking in local government: intervention design and adaptation in a community-based study - Tiana Felmingham; Siobhan O'Halloran; Jaimie Poorter; Ebony Rhook; Cindy Needham; Joshua Hayward; Penny Fraser; Stephanie Kilpatrick; Deana Leahy; Steven Allender (BMC, 2023)
Abstract Background Systems thinking approaches are increasingly being used by communities to address complex chronic disease. This paper reports on the VicHealth Local Government Partnership (VLGP) which sought to co-create improvements in the health and well-being of children and young people by working with local government in Victoria, Australia. Methods The VLGP included a series of health promotion modules, aimed at creating policy, programme and practice changes across local government. One of these modules, Connecting the Dots - creating solutions for lasting change, aimed to build capacity for systems thinking in municipal public health and well-being planning across 13 councils. The approach was adapted and data were collected on the stimuli for, and results of, adaptation. Results The council adapted the systems thinking approach to meet geographic characteristics, priority health issue/s and participant target group needs. Adaptions applied to workshop materials, training delivery, existing and new resources, and to align with other community-based approaches. Stimuli for adaptation included the COVID-19 pandemic, needs of children and young people, capacity of council to deliver the workshop series, and time available within the project or for the participant group. Conclusions Systems thinking was used and adapted by councils to improve the health and well-being of children and young people and increase the voices of children and young people in decision-making. Flexible delivery is critical to ensure communities can adapt the approach to meet local needs.